The health effects of universal early childhood interventions: Evidence from Sure Start - Sarah Cattan; Gabriella Conti; Christine Farquharson; Rita Ginja; Maud Pecher (Institute for Fiscal Studies (IFS), 2022)
Early Childhood Interventions (ECI) offering disadvantaged children preschool and family support services in the US show long-lasting health impacts. Can these benefits hold when these programs are offered to all children in contexts with universal healthcare? We evaluate the short- and medium-term health impacts of Sure Start, a universal integrated ECI in England, exploiting its 11-year rollout and administrative hospitalizations data. One additional Sure Start centre per thousand age-eligible children increases hospitalizations by 10% at age 1, but reduces them by 8-9% across ages 11-15. Impacts are concentrated in disadvantaged areas and likely driven by both health and non-health services.
Keywords: I10; I14; I18; 330; early childhood intervention; health; difference-in-differences